Analysis of a good image of the company - Babik, Yulia; Bozhok, Natalia (My University, 2014)
The image of the company is analyzed in the paper. The factors promoting the formation of positive image are defined.
Keywords: image; reputation; corporation; імідж; репутація; корпорація; кафедра ділової іноземної мови та міжнародної комунікації